h=-16t2+1053

Rewrite the equation as -16t2+1053=h.

-16t2+1053=h

Subtract 1053 from both sides of the equation.

-16t2=h-1053

Divide each term in -16t2=h-1053 by -16.

-16t2-16=h-16+-1053-16

Cancel the common factor of -16.

Cancel the common factor.

-16t2-16=h-16+-1053-16

Divide t2 by 1.

t2=h-16+-1053-16

t2=h-16+-1053-16

Simplify each term.

Move the negative in front of the fraction.

t2=-h16+-1053-16

Dividing two negative values results in a positive value.

t2=-h16+105316

t2=-h16+105316

t2=-h16+105316

Take the square root of both sides of the equation to eliminate the exponent on the left side.

t=±-h16+105316

Simplify the right side of the equation.

Combine the numerators over the common denominator.

t=±-h+105316

Rewrite -h+105316 as (14)2(-h+1053).

Factor the perfect power 12 out of -h+1053.

t=±12(-h+1053)16

Factor the perfect power 42 out of 16.

t=±12(-h+1053)42⋅1

Rearrange the fraction 12(-h+1053)42⋅1.

t=±(14)2(-h+1053)

t=±(14)2(-h+1053)

Pull terms out from under the radical.

t=±14⋅-h+1053

Combine 14 and -h+1053.

t=±-h+10534

t=±-h+10534

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

t=-h+10534

Next, use the negative value of the ± to find the second solution.

t=–h+10534

The complete solution is the result of both the positive and negative portions of the solution.

t=-h+10534

t=–h+10534

t=-h+10534

t=–h+10534

t=-h+10534

t=–h+10534

Solve for t h=-16t^2+1053